Symbolic Meaning of the Perak Api Tradition in the Mertak Tombok Village Community, Praya District, Central Lombok Regency - Winarta, Lalu Riyan; suud, suud; Nursaptini, Nursaptini (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The purpose of this study is to determine the symbolic meaning of the perak api tradition in the community of Mertak Tombok Village, Praya District, Central Lombok Regency. This study uses a qualitative approach with a case study method. The types of data used in this study are primary and secondary data with the research subjects being the community of Mertak Tombok Village, Praya District, Central Lombok Regency. The informants in this study were traditional leaders and anthropologists in Mertak Tombok Village, Praya District, Central Lombok Regency. The data collection techniques used in this study were observation, interviews, and documentation. Data analysis in this study was carried out in several stages, namely data reduction, data presentation, and conclusion drawing. The results of this study show that the symbolic meaning in the perak api tradition includes verbal symbols such as prayers of gratitude to Allah SWT and non-verbal symbols such as tools and materials, as well as the stages of implementation, namely rocking the baby over the smoke, the mother standing over the smoke or being covered, tying threads, massaging, holding the name, and presence.